PENGARUH TERPAAN TAYANGAN YOUTUBE DEDDY CORBUZIER TERHADAP PEMENUHAN KEBUTUHAN INFORMASI PADA PERILAKU KEKERASAN DALAM RUMAH TANGGA - Siti Adira Kania (2023)
Presenting information about domestic violence is currently being uploaded on social media, such as Deddy Corbuzier's YouTube. Shows about domestic violence on Deddy Corbuzier's YouTube are intended as a lesson for people who watch so that people understand about forms of domestic violence and how to deal with them, bearing in mind that the behavior of domestic violence in Indonesia is still increasing to date. The purpose of this study was to find out how much influence exposure to Deddy Corbuzier's YouTube shows has on fulfilling the need for information on domestic violence behavior. The theory used in this study is the uses and gratification theory by Elihu Katz, Jay G. Blumer, and Michael Gurevitch which explains how media exposure affects the fulfillment of the information needs of its users. This research method is explanatory quantitative with a survey method of 100 respondents to Deddy Corbuzier's YouTube subscribers. The sampling technique uses nonprobability sampling and purposive sampling techniques with predetermined respondent criteria. The results showed that the level of influence of Variable X (Exposure to Youtube Views) on Variable Y (Fulfillment of Information Needs) was 68.9%, so exposure to Deddy Corbuzier's YouTube shows had a large influence on fulfilling information needs.